Killer’s Fashion: Transforming the Potential of Nias Saber’s Amulets into Indonesian Fashion Accessories - Kezia Clarissa Langi; Setiawan Sabana; Hafiz Aziz Ahmad; Dian Widiawati (Humaniora, 2020)
The research was conducted to discover the potential of Nias saber’s amulets into fashion accessories and to introduce the tradition of Nias saber’s amulets into society. Nias war costume had its unique way of distinguishing each other and gaining a spiritual strength, which was to accessorize its war costume with small amulets. This tradition was a new inspiration for developing a fashion look with local identity. Exploring Indonesian culture in the form of fashion accessories was done in order to extract Indonesian potential in the fashion industry. Styling small ‘amulets’ into clothing could elevate one’s look while gaining a local meaning. The research applied a qualitative method with data collected through interviews, literature studies, and field research. The outcome of the research shows that Nias war costume’s amulet can be an inspiration for today’s fashion accessories that serve traditional meaning to the wearer.